The trouble with teacher turnover: How teacher attrition affects students and schools - Desiree Carver-Thomas; Linda Darling-Hammond (Arizona State University, 2019)
Addressing teacher turnover is critical to stemming the country's continuing teacher shortages. It is also important for school effectiveness, as the academic and financial costs of teacher turnover to student learning and district budgets are significant. Using the most recent nationally representative data from the National Center for Education Statistics' Schools and Staffing Surveys, the authors detail which teachers are leaving, why, and which students are most impacted. The study finds higher turnover rates in the South; among mathematics, science, special education, English language development, and world languages teachers; in schools serving students of color and from low-income families; and among teachers of color. The study also finds that several factors are associated with higher turnover rates, including lack of administrative support, teacher salaries, and alternative certification. The paper reviews policy strategies that can address teacher turnover.